2013
DOI: 10.1111/jar.12035
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Anger in Offenders and Non‐Offenders Who have Intellectual Disabilities

Abstract: Results suggest that there is no difference in levels of anger between offender and non-offenders to begin with. The limitations of the study are discussed, but the implication of the study questions the legitimacy of the rationale to utilize anger treatment to reduce recidivism in offenders with intellectual disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Similarly, individuals with ID and a higher number of co-morbid mental and physical health problems were at increased odds of displaying aggressive behaviour than those with fewer, less severe health problems (Crocker et al 2013); chronic sleep problems, visual impairment and incontinence may be of particular relevance (de Winter et al 2011). The role of anger in aggression for those with ID is less well supported; Nicoll and Beail (2013) found no difference in anger levels between offenders and non-offenders with ID. addition of these factors improves the ability of the HCR-20 to predict aggression among an ID population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, individuals with ID and a higher number of co-morbid mental and physical health problems were at increased odds of displaying aggressive behaviour than those with fewer, less severe health problems (Crocker et al 2013); chronic sleep problems, visual impairment and incontinence may be of particular relevance (de Winter et al 2011). The role of anger in aggression for those with ID is less well supported; Nicoll and Beail (2013) found no difference in anger levels between offenders and non-offenders with ID. addition of these factors improves the ability of the HCR-20 to predict aggression among an ID population.…”
Section: Discussionmentioning
confidence: 99%
“…). The role of anger in aggression for those with ID is less well supported; Nicoll and Beail () found no difference in anger levels between offenders and non‐offenders with ID. Future research should examine whether the addition of these factors improves the ability of the HCR‐20 to predict aggression among an ID population.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that offenders did not report greater scores on the majority of the variable examined was partly unexpected. Although some prior studies have also reported similar levels of negative emotionality, alexithymia, and emotion dysregulation in offenders and community participants (e.g., Donahue, McClure, & Moon, 2014;Nicoll & Beail, 2013;Strickland, Parry, Allan, & Allan, 2017), the average levels of alexithymia, impulsivity, and emotion dysregulation in our offender sample was lower than those of most studies that have also used self-report measures of these constructs (e.g., Roberton et al, 2014). One possibility for this finding is that conflating in our violent offender sample individuals who have committed offenses that varied in terms of severity of violence may have masked more nuanced differences between community participants and certain offender groups (Perley-Robertons, Helmus, Derkzen, & Serin, 2016).…”
Section: Preliminary Findings: Facet-level Group Differences and Bivamentioning
confidence: 91%
“…Set alongside the literature on drug treatment, there is some evidence that aggression by people with ID can be managed effectively by behavioural (British Psychological Society ; Brosnan & Healy ) or cognitive behavioural (Nicoll & Beail ; Willner et al . 2013a,b) interventions, including a recent large randomised controlled trial (Willner et al .…”
Section: Discussionmentioning
confidence: 99%
“…Set alongside the literature on drug treatment, there is some evidence that aggression by people with ID can be managed effectively by behavioural (British Psychological Society 2005; Brosnan & Healy 2011) or cognitive behavioural (Nicoll & Beail 2013;Willner et al 2013a,b) interventions, including a recent large randomised controlled trial (Willner et al 2013a,b). There is a complete absence of evidence as to whether people receiving risperidone who are non-psychotic -the majority (Tsiouris 2010;Paton et al 2011) -do better than they would if they received best-practice psychological support.…”
Section: Discussionmentioning
confidence: 99%